Ensino aprendizagem dos números inteiros no ensino fundamental : um olhar sobre as teses e dissertações produzidas no Brasil entre os anos de 2009 a 2019 - Cavalcante, Zillene Souza (2021)
This is a research work entitled Teaching and Learning Whole Numbers in Elementary School: A Look at the Theses and Dissertations produced in Brazil between the years 2009 to 2019. This research is connected to the Postgraduate Program in Education, from the Research Line of Research in Education and Science and Mathematics Education of the Postgraduate Program in Education, Master’s in Education at the Federal University of Mato Grosso, in Cuiaba. The general objective of this investigation is to present an overview of Master’s and Doctoral researches about the teaching and learning process of whole numbers between the years 2009 to 2019. The theoretical foundation is mainly centered on authors such as Freire (2013); Miguel and Miorim (2018); Silva (2009); D'Ambrosio (1998); Weevil (2005); Libâneo (2001); Tardif (2002), among others. It is also based on Fiorentini (1995), presenting a reflection on the main pedagogical trends that historically were/are being produced in Brazil. As a methodology, this research opted for a qualitative approach, a state-of-the-art type, and presents the analysis of 32 master's dissertations and 2 doctoral theses. Among the results, we can observe that the largest number of studies refers to the use of concrete and manipulable materials, games/problem solving/didactic sequences, and other activities, reaching 25 works; and the category with the lowest number of research is on Teacher Education with only 1 (one) study. Most of the surveys were carried out in Public Education Institutions – 82% and 18% in Private Institutions; another important data is in concern to the master's level: 56% are Professional Master's studies, and 44% are Academic Master's. The analysis is divided into five categories based on Bardin (2011): Textbook analysis; Use of Technologies, Concrete Materials, Games, Problem Solving, Didactic Sequences, and other activities; Use of History of Mathematics; Teacher Training and Difficulties and obstacles related to the teaching and learning process of whole numbers. About the challenges and questions, the importance of making researches that focus on the training of teachers who teach mathematics in elementary school is highlighted, as well as researches aimed at high school and education for young people and adults and also studies that can replicate successful researches already carried out, mainly those that use games, technological resources, problem-solving, and the use of the History of Mathematics.